2012
DOI: 10.1080/09540121.2012.726339
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of rapid HIV diagnosis technology among primary healthcare practitioners in Spain

Abstract: This study investigated the acceptability of rapid HIV testing among general practitioners (GP) and aimed to identify perceived barriers and needs in order to implement rapid testing in primary care settings. An anonymous questionnaire was distributed online to all members of the two largest Spanish scientific medical societies for family and community medicine. The study took place between 15 June 2012 and 31 October 2010. Completed questionnaires were returned by 1308 participants. The majority (90.8%) of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 17 publications
2
16
0
1
Order By: Relevance
“…Much of current research focuses on cost-effectiveness, feasibility, and acceptability of POC testing in one specific healthcare setting [4, 1216] or uses clinicians’ concerns regarding POC testing as potential indicators for uptake [15, 17]. Research on diagnostic processes, the role of POC tests for clinical and patient decision-making, and the adaptation of POC programs to various socio-cultural contexts is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Much of current research focuses on cost-effectiveness, feasibility, and acceptability of POC testing in one specific healthcare setting [4, 1216] or uses clinicians’ concerns regarding POC testing as potential indicators for uptake [15, 17]. Research on diagnostic processes, the role of POC tests for clinical and patient decision-making, and the adaptation of POC programs to various socio-cultural contexts is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative and quantitative survey-based studies have examined clinicians’ attitudes towards POC testing as a potential indicator for its uptake. The most common concerns raised by clinicians were test accuracy, over-reliance on tests, undermining of clinical skills, cost, limited usefulness [ 14 ], need for training and required counselling [ 15 ], as well as lack of time, interruption of workflow and complexity [ 16 ]. Yet, clinicians’ attitudes might not reflect their daily diagnostic practices or capture systemic challenges for POC testing across the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with those found in that study, and the fact that the time elapsed since the last test had no impact on them, make them trustworthy. Moreover, several studies, have examined physicians' perceived barriers to HIV testing; [11][12][13]18 these have found that two of the most common reasons given for not expanding HIV testing in general health services (primary care, hospital emergencies, etc.) are: first, lack of time, and second, perceiving themselves as not having the appropriate skills to address sexual behaviour and feeling discomfort in discussing HIV.…”
Section: Discussionmentioning
confidence: 99%